Epithelial Cell Packing Induces Distinct Modes of Cell Extrusions - Kocgozlu, Leyla; Saw, Thuan Beng; Le, Anh Phuong; Yow, Ivan; Shagirov, Murat; Wong, Eunice; Mège, René Marc; Lim, Chwee Teck; Toyama, Yusuke; Ladoux, Benoît (Current Biology, 2016)
The control of tissue growth, which is a key to maintain the protective barrier function of the epithelium, depends on the balance between cell division and cell extrusion rates [1, 2]. Cells within confluent epithelial layers undergo cell extrusion, which relies on cell-cell interactions [3] and actomyosin contractility [4, 5]. Although it has been reported that cell extrusion is also dependent on cell density [6, 7], the contribution of tissue mechanics, which is tightly regulated by cell density [8–12], to cell extrusion is still poorly understood. By measuring the multicellular dynamics and traction forces, we show that changes in epithelial packing density lead to the emergence of distinct modes of cell extrusion. In confluent epithelia with low cell density, cell extrusion is mainly driven by the lamellipodia-based crawling mechanism in the neighbor non-dying cells in connection with large-scale collective movements. As cell density increases, cell motion is shown to slow down, and the role of a supracellular actomyosin cable formation and its contraction in the neighboring cells becomes the preponderant mechanism to locally promote cell extrusion. We propose that these two distinct mechanisms complement each other to ensure proper cell extrusion depending on the cellular environment. Our study provides a quantitative and robust framework to explain how cell density can influence tissue mechanics and in turn regulate cell extrusion mechanisms.
CRIS-Team Scopus Importer:2024-02-19
Keywords: actin cytoskeleton; actomyosin purse-string; apoptosis; cell density; cell extrusion; epithelial cells; lamellipodium; mechanobiology